A large-scale study of anxiety and depression in people with Multiple Sclerosis: a survey via the web portal of the UK MS Register. - Kerina H Jones; David V Ford; Philip A Jones; Ann John; Rodden M Middleton; Hazel Lockhart-Jones; Lisa A Osborne; J Gareth Noble (PLoS ONE)
Introduction Studies have found that people with Multiple Sclerosis experience relatively high rates of anxiety and depression. Although methodologically robust, many of these studies had access to only modest sample sizes (N<200). The aims of this study were to use responses gained via the web portal of the UK MS Register (N>4000) to: describe the depression and anxiety profiles of people with MS; to determine if anxiety and depression are related to age or disease duration; and to assess whether the levels of anxiety and depression differ between genders and types of MS. Methods From its launch in May 2011 to the end of December 2011, 7786 adults with MS enrolled to take part in the UK MS Register via the web portal. The responses to the Hospital Anxiety and Depression Scale (HADS) were collated with basic demographic and descriptive MS data provided at registration and the resulting dataset was analysed in SPSS (v.16). Results The mean HADS score among the 4178 respondents was 15.7 (SE 0.117, SD 7.55) with a median of 15.0 (IQR 11). Anxiety and depression rates were notably high, with over half (54.1%) scoring ≥ 8 for anxiety and 46.9% scoring ≥ 8 for depression. Women with relapsing-remitting MS were more anxious than men with this type (p<0.001), and than women with other types of MS (p = 0.017). Within each gender, men and women with secondary progressive MS were more depressed than men or women with other types of MS (p<0.001, p<0.001). Conclusions This largest known study of its kind has shown that anxiety and depression are highly prevalent in people with MS, indicating that their mental health needs could be better addressed. These findings support service planning and further research to provide the best care for people with MS to help alleviate these debilitating conditions.